TANGGUNG JAWAB DIREKTUR UTAMA TERKAIT PELANGGARAN PRINSIP FIDUCIARY DUTY - Elvira Dewi Silvana; Arif Wicaksana (Reformasi Hukum Trisakti, 2022)
The rules that must be followed in line with the Articles of Association and Law Number 40 of 2007 regulating Limited Liability Companies place restrictions on the Board of Directors' capacity to administer the company. In practice, not all Directors actually follow the prevailing management ideas. The emergence of tax bill arrears is one example of how the Main Director of PT Bakara Bumi Energi violated the fiduciary duty concept by failing to report the company's financial accounts in a transparent way. The primary issue in this study is whether the Main Director of PT Bakara Bumi Energi violated the fiduciary duty concept and PT Bakara Bumi Energi's Main Director is accountable due to penetrating the corporate veil. Secondary data is the type of data employed in the normative juridical research type, which is descriptive in character. The study's findings were qualitatively examined by making deductions based on deductive reasoning. Because the President Director's management of the company was not based on good faith and was full of responsibility, it was determined that his actions constituted a violation of the fiduciary duty principle. He also failed to uphold the trust that the company had placed in him by being dishonest, opaque, and responsible for the company's losses.